Assessing the performance improvement of an intensified heat integration scheme: Reactive pressure-swing distillation. (5th February 2015) - Kiran, Bandaru; Jana, Amiya K.
Abstract: Declining petroleum reserves, increasing fuel demands and environmental problems have attracted increasing research attention in improving the energetic potential of separation processes dominated by distillation. In this contribution, we develop an intensified thermal integration scheme for a pressure-swing distillation (PSD) by combining the internally heat integrated distillation column (HIDiC) and the vapor recompression column (VRC), thereby acquiring the benefit of both of them. Since the PSD process typically combines a low-pressure (LP) and a high-pressure (HP) distillation unit, the possibility of thermal coupling arises between the HP column (heat source) and the LP column (heat sink) within the framework of HIDiC scheme. Aiming to further reduce the consumption of external energy in the PSD system, the overhead vapor of HP column is proposed to act as a heat source for bottom liquid reboiling in the LP column by the application of VRC mechanism. By this way, the HIDiC-VRC combination gets the shape of an intensified structure and it is capable of providing an enhanced energy efficiency potential. For a reactive pressure-swing distillation (reactive PSD), the proposed HIDiC-VRC configuration is shown to be more energy efficient and cost-effective compared to the HIDiC-alone scheme. Highlights: We develop an intensified heat integration scheme. It introduces vapor recompression in an internal heat integration configuration. An open-loop control mechanism is devised for optimal use of internal heat sources. A pressure-swing distillation is simulated to illustrate the intensified scheme.